Village Head's Efforts to Prevent Stunting: Strategy for Providing Additional Menus as a Child Health Solution - Nurkholisa, Eka; Thohir, Muhammad; Mardiyah, Mardiyah (Universitas Ibn Khaldun, 2024)
This research aims to determine the role of the Jaladri village head in preventing stunting by providing effective additional menus, especially for poor families who are vulnerable to malnutrition. With a descriptive qualitative approach, this research shows that village heads play an important role in improving the nutritional status of children in the village. Additional menus are designed to meet nutritional needs that support children's optimal growth. Research recommendations emphasize the need to improve national nutrition policies that are more integrated and effective. A comprehensive and sustainable approach is needed in stunting prevention programs throughout Indonesia, including nutrition education, access to additional menus, as well as strengthening the health system and support from various parties, including village governments. It is hoped that this effort can have a positive impact in reducing stunting and improving the quality of children's nutrition.